2014
DOI: 10.5137/1019-5149.jtn.11549-14.0
|View full text |Cite
|
Sign up to set email alerts
|

Epidural anesthesia in elective lumbar microdiscectomy surgery: is it safe and effective?

Abstract: AIm:The aim of this study was to evaluate effectiveness and safety of epidural anesthesia in elective lumbar microdiscectomy surgery. mATErIAl and mEThOds: Twenty-seven patients (78%, female), who were admitted for single level simple microdiscectomy surgery between May 2012 and December 2013 in single spine center of a university hospital, were enrolled into the study. Clinical evaluations with demographical and per-operative data were collected prospectively. rEsulTs: Mean age was 60.04 years. Mean weight, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…However, studies in the literature have suggested that the concentration of ropivacaine used plays an important role in the alleviation of pain. 26 Kathuria 27 and Zhu 28 et al separately reported that low concentrations of ropivacaine (0.25% or 0.375%) blocked the sensory nerves without completely blocking the motor nerves, resulting in better efficacy in pain management when used in EA. Previously, with the help of anesthesiologists, we tested concentrations of ropivacaine ranging from 0.1% to 0.375% according to the physical condition of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in the literature have suggested that the concentration of ropivacaine used plays an important role in the alleviation of pain. 26 Kathuria 27 and Zhu 28 et al separately reported that low concentrations of ropivacaine (0.25% or 0.375%) blocked the sensory nerves without completely blocking the motor nerves, resulting in better efficacy in pain management when used in EA. Previously, with the help of anesthesiologists, we tested concentrations of ropivacaine ranging from 0.1% to 0.375% according to the physical condition of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients could also move their lower limbs when the surgeons required to identify nerve injury. On the other hand, literatures have suggested the concentration of ropivacaine played important role in the alleviation of pain 24 . Kathuria 25 and Zhu 26 et.al separately…”
Section: Discussionmentioning
confidence: 99%
“…Epidural anesthesia (EA) is another anesthesia method that allows patients to remain conscious. 11 However, nerve injury occurred in PELD using EA as before. A single-center retrospective analysis found that the incidence of nerve root injury in PELD using EA was 1.2% (5/426); 12 another study reported, an 8.6% (30/233) incidence.…”
Section: Introductionmentioning
confidence: 89%